Analysis of micro and macro marketing environment in the juice market - Krutikova, A. (ТДАТУ, 2018)
Natural juice has a therapeutic effect. Our body receives a lot of vitamins, trace elements, minerals with various juices. Today, there is a strong competition in the juice market. For effective work of the enterprise, it is necessary to constantly explore the macro and micro environment of the market.
Keywords: market; marketing; mineral water; managerial; functional